Vertical structure of the Arctic spring transition in the middle atmosphere - Matthias, Vivien; Stober, Gunter; Kozlovsky, Alexander; Lester, Mark; Belova, Evgenia; Kero, Johan (2020)
In the middle atmosphere, spring transition is the time period where the zonal circulation reverses from westerly in winter to easterly in summer which has a strong impact on the vertical wave propagation influencing the variability of the ionosphere. The spring transition itself can be rapid in form of a final sudden stratospheric warming (SSW, mainly dynamically driven) or slow (mainly radiatively driven) but also intermediate stages can occur. Many studies investigate the spring transition by first defining an onset day (e.g., the zonal mean zonal wind reversal at 10hPa and 60°N) and then dividing all available spring transitions into early and late occurring spring transitions. However, all these studies focus exclusively on the stratosphere and give only tendencies under which pre-winter conditions an early or late spring transition takes place and how it takes place (rapid or slow). Here we classify the spring transitions regarding their temporal development beginning in January of the same year and additionally regarding their vertical structure in the stratosphere and mesosphere in the core region of the polar vortex. This leads to five classes where the timing of the SSW as well as a downward propagating Northern Annular Mode (NAM) plays a crucial role. First we use MLS satellite data to describe the five classes for recent single years, and then we use MERRA2 reanalysis data for a composite analysis. The results show distinctive differences between the five classes in the months before the spring transition especially in the mesosphere. This allows a certain prediction at least for some of the five classes of spring transition. Additionally, some of the spring transitions have a very special vertical structure in the mesosphere theoretically filtering out every wave from the lower atmosphere. The impact of these spring transitions on the ionospheric variability is discussed.